Impurities and Forced Degradation Studies: A Review - Kogawa, Ana C. [UNESP]; Salgado, Herida R. N. [UNESP] (Bentham Science Publ Ltd, 2016)
The safety of pharmaceuticals is dependent not only on the intrinsic toxicological properties of the active ingredient, but also on the impurities and degradation products that it may contain. The presence of impurities in active ingredients can have a significant impact on the quality, safety and efficacy of pharmaceuticals. Efforts should be made to identify and characterize all unknown impurities in the drug, due to the increasing demand of regulatory agencies to manufacture high-purity drugs. The drug impurity profile is one of the most important issues in modern pharmaceutical analysis during the process of technology development for the production of high-purity substances. The degradation products may be provided through forced degradation studies, which enable development of indicators of stability methods with appropriate specificity and selectivity, purity verification chromatographic peak of active pharmaceutical ingredient in the product, provides information about possible degradation routes of a certain product, evaluation of the factors that may interfere in any way in the drug stability and critical analysis of the drug degradation profile.
Keywords: Degradation products; degradation profile; forced degradation; impurities; quality; pharmaceuticals